1998
DOI: 10.1021/ci970030u
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Moments of the Edge Adjacency Matrix in Molecular Graphs. 3. Molecules Containing Cycles

Abstract: A substructural approach to quantitative structure−property relationships based on the spectral moments of the edge adjacency matrix is extended to molecules containing cycles. Spectral moments are expressed as linear combinations of structural fragments of any kind of nonweighted graphs. The boiling points of a series of 80 cycloalkanes was well-described by the present approach. The predictive power of the model was proved by using a test set of another 26 compounds. An equation that expresses the contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
109
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 15 publications
0
109
0
1
Order By: Relevance
“…It is known as the TOPS-MODE approach, which is the acronym for topological substructural molecular descriptors/design (Estrada, 1996;Estrada, 1998;Estrada & Uriarte, 2001;Estrada et al, 2000). The TOPS-MODE approach is based on the calculation of spectral moments of molecular bond matrices appropriately weighted to account for hydrophobic, electronic and steric molecular features.…”
Section: Qsar Studies Under Tops-mode Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known as the TOPS-MODE approach, which is the acronym for topological substructural molecular descriptors/design (Estrada, 1996;Estrada, 1998;Estrada & Uriarte, 2001;Estrada et al, 2000). The TOPS-MODE approach is based on the calculation of spectral moments of molecular bond matrices appropriately weighted to account for hydrophobic, electronic and steric molecular features.…”
Section: Qsar Studies Under Tops-mode Approachmentioning
confidence: 99%
“…the sum of all entries in the main diagonal of such matrices. The reader is referred to (Estrada, 1996;Estrada, 1998) to obtain full details of this method.…”
Section: Qsar Studies Under Tops-mode Approachmentioning
confidence: 99%
“…Such parameters can be assigned as relevant in the context of skin sensitisation in that partition could be modelled by hydrophobicity, polar surface area, molar refractivity, van der Waals radii as bulk parameters and the reactivity accounted for by polarisability and charges. The Topological SubStructural Molecular Design (TOPS-MODE) approach used in this example is based on the method of moments (Estrada, 1996(Estrada, , 1997(Estrada, , 1998. The approach consists of using the topological bond matrix (edge adjacency matrix) of the molecular graph.…”
mentioning
confidence: 99%
“…It is known as TOPS-MODE approach, which is the acronym for topological substructural molecular descriptors/design [57][58][59][60][61][62]. TOPS-MODE approach is based on the calculation of spectral moments of molecular bond matrices appropriately weighted to account for hydrophobic, electronic and steric molecular features.…”
Section: Methodology 31 the Tops-mode Approachmentioning
confidence: 99%
“…An automatic knowledge generator is a methodology that will provide new structural alerts to the knowledge archive in a cyclic way keeping it updated. In previous works [54][55][56] we have shown that the so-called topological sub-structural molecular design (TOPS-MODE) approach [57][58][59][60][61][62] represents a useful platform for the automatic generation of toxicological structural alerts. In these works a general strategy for knowledge flow concerning skin sensitization and chromosome aberrations based on the combined use of TOPS-MODE and DEREK expert system was proposed [54][55][56].…”
Section: Necessity For Automated Rule-extractionmentioning
confidence: 99%